2022
DOI: 10.22270/jddt.v12i3.5468
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic and Pharmacological Efficacy of Achyranthes aspera Linn.: An Updated Review

Abstract: Achyranthes aspera is an erect perennial herb that comes under the family Amaranthaceae. The plant and its parts are traditionally used to cure several diseases such as renal dropsy, hemorrhoids, dysentery, asthma, cough, stomach ache, skin eruptions, diarrhea, dysentery, stimulating labor pain, nose-bleeding, snake-bites, nose bleeding and dilating blood vessels. Secondary metabolites such as alkaloids, saponins, tannins, flavonoids, glycosides, steroids, essential oil and fatty acids play a significant role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Achyranthine is a water-soluble alkaloid from A.aspera and has been shown to have blood vessel dilatation and hypotension effects. 42,43 Previous studies have shown that the saponins found in the seeds of A.aspera have a better capacity to scavenge ABTS free radicals. 44 Numerous studies revealed the A.aspera sensitivity to the antibacterial effects against B.subtilis, K.pneumoniae, M.luteus, P.aeuroginosa, S.aureus, E.coli, chloerasuis, and S.pyogenes and antifungal action against F.oxysporum, R.solani, S.rolfsii, Alternaria sp., S.cerevisae, C.albicans, A.nigricans, F.oxysporum, Candidia sp.…”
Section: Achyranthes Aspera Lmentioning
confidence: 99%
“…Achyranthine is a water-soluble alkaloid from A.aspera and has been shown to have blood vessel dilatation and hypotension effects. 42,43 Previous studies have shown that the saponins found in the seeds of A.aspera have a better capacity to scavenge ABTS free radicals. 44 Numerous studies revealed the A.aspera sensitivity to the antibacterial effects against B.subtilis, K.pneumoniae, M.luteus, P.aeuroginosa, S.aureus, E.coli, chloerasuis, and S.pyogenes and antifungal action against F.oxysporum, R.solani, S.rolfsii, Alternaria sp., S.cerevisae, C.albicans, A.nigricans, F.oxysporum, Candidia sp.…”
Section: Achyranthes Aspera Lmentioning
confidence: 99%
“…The prickly chaff flower, also known as A. aspera, is an annual plant that grows in tropical and subtropical climates 41 . Studies about A. aspera plant leaves have shown that they contain several active compounds, including alkaloids, flavonoids, tannins, and saponins 42 .…”
Section: Achyranthes Asperamentioning
confidence: 99%